Pengaruh Profitabilitas, Likuiditas Dan Ukuran Perusahaan Terhadap Return Saham Pada Perusahaan Food And Beverages Di Bursa Efek Indonesia - Ganerse, I Made Brian; Suarjaya, Anak Agung Gede (E-Jurnal Manajemen; Vol 3 No 6 (2014), 2014)
Important information for investors to make investment decisions reflected in the financial statements. Investors must expect a high rate of return on the funds invested into the company. The purpose of this study was to determine the effect of profitability, liquidity, and firm size on stock returns of food and beverages companies the period 2008-2011. Criteria through the purposive sampling method then obtained a sample of 16 companies in the food and beverages sector. Multiple linear regression analysis techniques were used obtain the result that the profitability of a significant positive effect on stock returns, no significant effect of liquidity on stock returns and firm size are significant positive influence on stock returns. Keywords: stock return, profitability, liquidity, company size